Praktik Sosial Perempuan dalam Pengembangan Usaha Batik Madura Desa Tanjungbumi Bangkalan - Syarifudin, Achmad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Batik is not only an economic commodity, but also a cultural heritage. The ecosystem for women batik business actors carrying out their business activities is not yet optimal, and does not depend on economic capital but is seen as a social process that is accumulative of habitus, capital and various arenas. It is necessary to examine further the social practices of women in the development of the Madurese batik business in Tanjungbumi Village, Bangkalan. This research method uses a case study, carried out in Tanjungbumi Village during October-November 2023. The research informants are women who are entrepreneurs in the Madurese batik business. The data analysis technique used is a descriptive case study. The research results show that women's repeated social practices are strongly influenced by realities inside and outside the individual, namely knowledge, skills, social networks, promotional media and batik market share, which play an important role in social practices in the production, distribution and consumption arenas. The conclusion of research on women's social practices in developing the Madurese batik business in Tanjungbumi Village has not been optimal in creating a supportive ecosystem for batik business actors.